Effect of Microbial Cell-Free Supernatants Extracted From a Range of pH Levels on Corn (Zea mays L.) and Tomato (Solanum lycopersicum L.) Seed Germination and Seedling Growth - Msimbira, Levini A.; Naamala, Judith; Antar, Mohammed; Subramanian, Sowmyalakshmi; Smith, Donald L. (Frontiers in Sustainable Food Systems, 2022)
The negative effects of more extreme pH conditions (soil acidity and alkalinity) are increasingly challenging crop production. Managing acidity and alkalinity in soils has been achieved through techniques such as the use of lime, afforestation, tillage and addition of organic matter. The use of microbes to address this challenge is new and could increase agroecosystem sustainability while helping plants survive more extreme acidity and alkalinity, among other stresses. Use of plant growth promoting microbes (PGPM) has recently gained attention as these microbes afford plants several benefits, including nutrient acquisition and stress tolerance, both biotic and abiotic. Several methods of microbe application have been developed, all intended to maximize the benefits of plant-microbial interactions. The current study assessed the potential of changing microbial culture pH during production, followed by removal of cells to produce supernatant that enhances plant growth, specifically under acidity and alkalinity stresses. The study included Lactobacillus sp. (EL2006H) and Bacillus sp. (EB2004S) which were cultured at three pH levels (5, 7 and 8) incubated for 24 - 48 h then centrifuged at 12 000 g to remove the cells. The cell-free supernatants obtained were used for seed germination and early seedling growth assays. The results indicated significant increase in seed germination rate, for both corn and tomato, compared experimental controls. Supernatants produced at pH 5, for both strains, had greater effect than those produced at pHs 7 and 8. Similarly, the positive effect of these supernatants was observed in seedling growth as increased root length and volume. Their results indicate that there is potential in stressing microbes below or above optimum pH ( 7) to induce production and excretion of favorable materials into the growth medium, as was evident in this study. To the best of our knowledge this would be the first attempt to look at this pH change to increase potential benefits related to plant growth promotion by microbes. It was interesting to learn that using the CFS of microbes cultured at pH 5 increased germination rate and seedling growth. These results provide an initial indication that support broadened research into PGPM under pH stressed conditions.